Developing aerobic power and capacity for combat sports athletes - Ursula Ferreira Julio (Universidad de León, 2021)
This chapter describes the physiological responses associated with aerobic power and capacity of combat sports athletes from different modalities (judo, Brazilian jiu-Jitsu, wrestling, Olympic boxing, taekwondo, karate and muay-thai) during specific and non-specific situations. Moreover, we describe the most used methods for the control and monitoring of these variables. Finally, the longitudinal studies that investigated the effects of aerobic power and capacity training for combat sports athletes are descripted.